Characterization of Europium and Americium Dipicolinate Complexes - Heathman, C. R.; Nash, K. L. (Separation science and technology, 2012)
Dipicolinic acid (pyridine-2,6-dicarboxylic acid, DPA) is a well-known complexant that forms moderately strong complexes with a variety of metal ions, including trivalent lanthanides. A search of open literature reports and thermodynamic databases produced no information on equilibrium constants for dipicolinate complexes of trivalent actinides. Such information represents an essential starting point for assessing the potential for application of dipicolinate to the task of trivalent lanthanide/actinide separations, specifically as a potential substitute for diethylenetriamine-N,N,N′,N″,N″-pentaacetic acid (DTPA) in the TALSPEAK process. The Am(III)/Eu(III)-dipicolinate system is the subject of the following report. Protonation constants of dipicolinic acid are pK 1 = 2.15 (±0.02) and pK 2 = 4.62 (±0.02) in µ = 1.0 M NaClO 4 media, T = 25.0 (±0.1)°C. Stability constants of Eu 3+ and Am 3+ with DPA have been determined using solvent extraction distribution methods coupled with radiometric detection. The resolved americium stability constants are log β 101 = 8.90 (±0.02), log β 102 = 15.87 (±0.03), and log β 103 = 21.88 (±0.04), while the corresponding europium constants are log β 101 = 8.90 (±0.02), log β 102 = 15.64 (±0.03), and log β 103 = 21.65 (±0.04) under the same conditions. Stability constants were fit using weighted non-linear least squares analysis of multiple distribution experiments conducted as a function of pH. A preliminary assessment of the separation potential of dipicolinic acid in TALSPEAK-like systems is offered.